2020
DOI: 10.3390/ijerph17249356
|View full text |Cite
|
Sign up to set email alerts
|

“It Changes Your Orbit”: The Impact of Suicide and Traumatic Death on Adolescents as Experienced by Adolescents and Parents

Abstract: Background: Having someone close die through suicide or another form of traumatic death is a distressing event in the lives of adolescents, putting them at risk of grief and mental health ramifications. As most research in this field has been focused on intrapersonal grief reactions, this study aimed to broaden the perspective by exploring the impact of the death through an interpersonal lens. Methods: The study involved individual and group interviews with bereaved adolescents (n = 20) and parents of bereaved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 90 publications
5
30
0
1
Order By: Relevance
“…While translation of research findings into practice remains challenging, research should be informed by clinical experience, as well as the experiences of bereaved adolescents and families, to be clinically relevant and to address the needs of the bereaved adolescents. Our research with bereaved adolescents and parents revealed that bereaved adolescents value a genuine relationship with a helping professional and want to feel understood [15,20]. In addition, they want to maintain control over the counseling process and be able to access services when they need it.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…While translation of research findings into practice remains challenging, research should be informed by clinical experience, as well as the experiences of bereaved adolescents and families, to be clinically relevant and to address the needs of the bereaved adolescents. Our research with bereaved adolescents and parents revealed that bereaved adolescents value a genuine relationship with a helping professional and want to feel understood [15,20]. In addition, they want to maintain control over the counseling process and be able to access services when they need it.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, deidentified transcripts from 28 individual and 11 group interviews, with a total of 20 bereaved adolescents, 18 parents/guardians of a bereaved adolescent, and 34 counsellors, conducted in the APC study [15] were reviewed for statements regarding how a helping professional should help a bereaved adolescent. One researcher (AR) read the transcripts and extracted the relevant statements.…”
Section: Sourcing Statementsmentioning
confidence: 99%
See 3 more Smart Citations